The four seasons of pancreatitis – Etiology of acute pancreatitis during the course of the year - Sirtl, Simon; Hohmann, Eric; Beyer, Georg; Hamm, Jacob; Neesse, Albrecht; Ammer-Herrmenau, Christoph (Zeitschrift für Gastroenterologie, 2024)
Background/Objectives Whether seasonality is a factor that influences the incidence of acute pancreatitis (AP) is an under-investigated area. If seasonal incidence peaks can be detected, specifically with regard to biliary pancreatitis, has so far been answered in contradictory ways in the literature.Methods All AP cases from two tertiary German referral centers were identified between 2016 and 2022 based on ICD-10 discharge codes. The χ2 test for goodness of fit was applied to test significant differences in monthly and seasonal distributions of AP admissions.Results In total, 3597 AP cases were included. We observed significantly more idiopathic and biliary cases in May to July (p-values 0.041 and 0.027, respectively). Furthermore, most drug-induced APs were identified during the winter months (p-value 0.006). Moreover, there was a significant peak of alcohol-induced pancreatitis in summer and fall (p-value 0.038).Conclusions Our data indicate a seasonal impact on AP incidences for certain etiologies.
Keywords: Acute pancreatitis; seasonality; idiopathic pancreatitis; biliary pancreatitis